Diversity, Distribution and Phylogenetic Relationships of Deep-Sea Lithistids (Porifera, Heteroscleromorpha) of the Azores Archipelago - Xavier, Joana R.; Rees, David J.; Pereira, Raquel; Colaço, Ana; Pham, Christopher K.; Carvalho, Francisca C. (Frontiers in Marine Science, 2021)
Lithistid sponges are globally distributed in temperate and sub-tropical areas, constituting an important component of deep-sea benthic communities where they form structurally complex and vulnerable marine ecosystems (VMEs). In this study, we assess the diversity and investigate the spatial and bathymetric distribution of the lithistid sponges of the Azores archipelago (North Atlantic) based on historical records and examination of samples accidentally collected during deep-sea longline fishing operations in the region. Eleven lithistid species are recognized to occur in the Azores, including Leiodermatium tuba, recently described from material collected in several Northeast Atlantic seamounts that is hereby reported for the first time to the archipelago. We provide molecular barcodes (mtDNA COI and rRNA 28S) for seven of these species, including Discodermia ramifera, Macandrewia azorica, and Exsuperantia archipelagus, for which the Azores constitutes the type locality. We further discuss the phylogenetic and biogeographic affinities of the Azorean lithistids in the context of the Porifera classification, and the wider Northeast Atlantic upper bathyal fauna. Our study also warrants the addition of some lithistid species to the list of VME indicators for the Northeast Atlantic in support of the sustainable management and conservation of these species and habitats, as well as the ecological functions they deliver.